Self-reported psychological symptoms and severe stress events, but not patients' gender, affect illness representation and medical advice by lay-referral network advisors. (March 2023) - Giovannelli, Ilaria; Pagliaro, Stefano; Spaccatini, Federica; Pacilli, Maria Giuseppina
Abstract: People who experience symptoms tend to discuss their ailments with other individuals who create their own illness representations, acting as intuitive physicians. We conducted two experimental studies to examine lay-referral network advisors' (i.e., acquaintances) representation of illness etiology and their recommendation to undergo health screenings for a man or woman with physical (vs. both physical and psychological) symptoms and a severe stressful (vs. no stressful) period in life. The presence of psychological and physical symptoms (Studies 1 and 2) and severe stressful life events (Study 2) affects lay-referral network advisors' disease representation. These factors cause participants to attribute symptoms etiology to psychological rather than organic factors and recommend more psychological screenings rather than physical ones. The simultaneous presence of psychological and physical symptoms and severe stressful events increases the likelihood of attributing the illness etiology to psychological factors, which increases participants' willingness to recommend psychological screenings. Study variables were unaffected by patient gender. The main findings, limitations, and future directions are discussed. Highlights: Psychological symptoms and stressful events affect illness etiology and medical advice. Etiology works as a mediator between symptoms, life events, and medical advice. Study variables were unaffected by patient's gender.